Systematic Participation in Folk Dance or Physical Activity? Effects in Quality of Life in the Elderly - Zisi Βασιλική; Gianni Αικατερίνη; Bougiesi Μαρία; Pollatou Ελιζάνα; Michalopoulou Μαρία (Inquiries in Physical Education and Sport, 2014)
The traditional Greek dance is a physical activity with many benefits for the psychological and physical health of dancers. The purpose of the present study was to investigate if older people who participate in activities related to Greek traditional dance show higher levels of quality of life compared with people of the same age, who follow sedentary life or participate in another type of physical activity. The participants were 150 people (57 men, 93 women) from 60 to 70 years old, randomly selected from different areas of Greece, so that to correspond to one of the three, equal in number, groups: traditional dancers, exercisers and sedentary. The participants completed the SF-36 questionnaire for quality of life measures. According to one-way MANOVA analysis, there was a significant main effect of the group, with dancers scoring higher than the two other groups on the factors of Physical Functioning (p<.001), Physical Role (p<.001), Bodily Pain (p<.001), General Health (p<.001), Vitality (p<.001), Social Functioning (p<.001), Role Emotional (p<.001), and Mental Health (p<.001). It seems that traditional Greek dance offers a lot of benefits for aged persons, since it is not only a kind of physical activity that makes them feel better, but also improves many aspects of their quality of life.